2023
DOI: 10.1038/s41598-023-30040-0
|View full text |Cite
|
Sign up to set email alerts
|

Three-decade assessment of dry and wet spells change across Iran, a fingerprint of climate change

Abstract: Extended periods of hydro-climate extremes with excessive or scarce rainfall associated with high or low temperatures have resulted in an imbalanced water cycle and inefficient socio-economic systems in several regions of Iran. However, there is a lack of comprehensive investigations on short-term to long-term variations in timing, duration, and temperature of wet/dry spells. This study bridges the current gap through a comprehensive statistical analysis of historical climatic data (1959–2018). Results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…It is worth mentioning that the heatwaves odds experienced insignificant (P value > 0.05) changes for 23% of stations, including Abadan, Arak, Birjand, Urmia, Zahedan, and Zanjan. Other studies confirmed similar positive tendencies in heatwaves characteristics, summer temperature, and maximum dry spell temperature in different regions around the world (Basha et al, 2017;Deng et al, 2018;He et al, 2022;Jamali et al, 2022;Jyoteeshkumar Reddy et al, 2021;Motamedi et al, 2023;Sato & Nakamura, 2019;Trancoso et al, 2020).…”
Section: Heatwave Duration and Heating Ratesupporting
confidence: 65%
See 1 more Smart Citation
“…It is worth mentioning that the heatwaves odds experienced insignificant (P value > 0.05) changes for 23% of stations, including Abadan, Arak, Birjand, Urmia, Zahedan, and Zanjan. Other studies confirmed similar positive tendencies in heatwaves characteristics, summer temperature, and maximum dry spell temperature in different regions around the world (Basha et al, 2017;Deng et al, 2018;He et al, 2022;Jamali et al, 2022;Jyoteeshkumar Reddy et al, 2021;Motamedi et al, 2023;Sato & Nakamura, 2019;Trancoso et al, 2020).…”
Section: Heatwave Duration and Heating Ratesupporting
confidence: 65%
“…Over the past decades, numerous studies have indicated that climatic records exhibit some non‐stationarity characterized by trends and shifts (Gohari et al., 2022; Jamali et al., 2022; Motamedi et al., 2023; Rougé et al., 2013; Ruibal‐Conti et al., 2013; Wagesho et al., 2012; Y. Wang et al., 2021). Several approaches, such as frequency analysis with time‐varying distribution functions, have been proposed to tackle non‐stationarity in hydrometeorological and climatological extremes (Ju et al., 2021; Lee et al., 2020; Ouarda et al., 2019; Ragno et al., 2019; Sarhadi & Soulis, 2017; Sun et al., 2022; Vinnarasi & Dhanya, 2022; Vu & Mishra, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Drylands in Iran are likely to be affected more adversely than other countries in the Middle East [10], with predictions of increasing frequency and duration of extremely dry periods and extremely hot days [11]. These trends have already been identified in climatic records when comparing the two 30-year periods between 1959 and 2018 [12]. Since 1970 in the arid rangelands of Khorasan (southeastern Iran), annual rainfall variability has increased along with a rising precipitation index, indicating greater risk of droughts and intense rainfalls [13].…”
Section: Introductionmentioning
confidence: 91%
“…Iran is particularly vulnerable to climate change because about 33.5% of its agricultural land (6.2 million hectares) is rainfed, and 76% of the rainfed area receives less than 400 mm of annual rainfall [8]. Iran is expected to experience an increase of 2.6 • C in mean temperatures and a 35% decline in precipitation in the next several decades [9] and there is evidence of a downward trend in precipitation in recent decades [10][11][12]; therefore, there is a need to increase the resilience of crops to reduce the effect of the frequent intensive dry episodes [13].…”
Section: Introductionmentioning
confidence: 99%